Managemental perspectives in livestock production system associated with the reduction of antibiotic usage in veterinary practices: Bangladesh perspectives (Asian-Australasian Journal of Bioscience and Biotechnology, 2018)
Antibiotic drugs have identified to be one of the most valuable tools in preserving both human and animal health. With an increase in the use and availability of antibiotics, antibiotic residues in animal origin food as well as antibiotic resistance have become important public health concern and have received much attention from government agencies, consumer level, media and other concerned public interest groups. The main objectives of the study were to identify the managemental perspectives in livestock production system associated with the reduction of antibiotic usage in veterinary practices so that the development of relevant strategies for reducing antibiotic usage in veterinary practices could be achieved in context of environmental realities in Bangladesh. The survey was interpretive in nature using quantitative methods. A non-experimental and descriptive research design was used to conduct this study. The survey study was carried out at existing seven divisions (i.e. Rangpur, Rajshahi, Khulna, Dhaka, Sylhet, Barishal and Chittagong/ Chattogram) in Bangladesh during July, 2012 to June, 2018 (upto final reporting) by survey method using close ended questionnaires among randomly selected respondents (i.e. 390 Government Veterinary Surgeons as well as 390 Upazila Livestock Officers of DLS, Bangladesh). Survey instruments were also designed to capture the perspectives of two different groups of government veterinarians: Group 1– Veterinary Surgeons of DLS, Bangladesh and Group 2 – Upazila Livestock Officers of DLS, Bangladesh.  Collected data were analyzed using SPSS (version 20.0, SPSS Inc., Chicago, IL) software. The findings indicated the knowledge, beliefs and perceptions of respondents. The research findings divulge that different managemental perspectives/dimensions in livestock production system associated with regular veterinary examination, allocation of appropriate nutrition, routine vaccination, arrangement of effective bio-security, use of probiotics, supply of hygienic water, arrangement of holistic therapies, arrangement of clean bedding as well as hygienic housing management, use of organic acids (e.g. Formic, acetic and propionic acids), use of plant extracts (e.g. essential oils of thyme, clove, turmeric, black pepper etc.) in poultry feed, use of prebiotics like Fructo Oligosaccharides(FOS), Manna Oligosaccharides(MOS) etc. in poultry feed, arrangement  of hygienic as well as good quality feed management and maintaining hygienic air quality in the farming system had ‘moderate to substantial role’ in livestock production system for reducing antibiotic usage in veterinary practices in Bangladesh.  Findings also indicated that the two groups of veterinarians possessed near to similar/same perceptions across different managemental perspectives in livestock production system associated with the reduction of antibiotic usage in veterinary practices in Bangladesh and that no significant differences in perspectives existed (p> .05). Findings of this study could be implemented for formulation of effective policy as well as guideline with the development of relevant strategies for reducing antibiotic usage in veterinary practices for development of sustainable livestock production system in Bangladesh.Asian Australas. J. Biosci. Biotechnol. 2018, 3 (3), 182-189